MHC class I transactivator NLRC5 in host immunity, cancer and beyond. Issue 3 (3rd August 2020) - Cho, Steven X.; Vijayan, Saptha; Yoo, Ji‐Seung; Watanabe, Toshiyuki; Ouda, Ryota; An, Ning; Kobayashi, Koichi S.
Summary: The presentation of antigenic peptides by major histocompatibility complex (MHC) class I and class II molecules is crucial for activation of the adaptive immune system. The nucleotide‐binding domain and leucine‐rich repeat receptor family members CIITA and NLRC5 function as the major transcriptional activators of MHC class II and class I gene expression, respectively. Since the identification of NLRC5 as the master regulator of MHC class I and class‐I‐related genes, there have been major advances in understanding the function of NLRC5 in infectious diseases and cancer. Here, we discuss the biological significance and mechanism of NLRC5‐dependent MHC class I expression. Abstract : CITA (MHC class I transactivator)/ NLRC5 is a transcriptional co‐activator of MHC class I and related genes. NLRC5 plays critical roles in defense against viral infection and cancer through activation of CD8 T cells. The genetic and epigenetic changes in NLRC5 serve as immune evasion mechanisms in multiple cancer types.